The Practice of Remarriage After Divorce Outside the Religious Court: A Case Study in Tatengger Village Angkola Muara Tais Subdistrict - Dinda Asrona; Ibrahim Siregar; Uswatun Hasanah (Islamic Circle, 2025)
Divorce outside the Religious Court is still a common practice among Muslim communities, including in Tatengger Village, Angkola Muara Tais District, and raises further legal issues regarding marital status and remarriage practices. This study aims to analyze the implementation of remarriage after divorce outside the Religious Court and review it from the perspective of Islamic law and Indonesian positive law. This study uses a qualitative method with a normative and empirical juridical approach, through field studies and literature studies. Data was obtained through interviews with married couples, religious leaders, and community leaders, then analyzed descriptively and analytically. The results of the study show that remarriage is carried out as a form of precaution (Ihtiyati) to maintain the validity of the husband and wife relationship due to doubts about the status of divorce. In Islamic law, this practice is related to the concept of Tajdid Al-Nikah, which has certain legal implications, while in positive law, this practice has no legal force and has the potential to cause legal uncertainty. This study emphasizes the need for harmonization between Islamic law and state law in family law practice.